2014
DOI: 10.2135/cropsci2012.11.0658
|View full text |Cite
|
Sign up to set email alerts
|

Quality Protein Maize Germplasm Characterized for Amino Acid Profiles and Endosperm Opacity

Abstract: Quality protein maize (QPM) is improved over normal (non‐QPM) maize in grain concentrations of the essential amino acids lysine and tryptophan. Quality protein maize has a long history as tropical adapted germplasm, but little effort has been made to incorporate temperate or sub‐tropical germplasm for temperate adaptation and interactions between different modifier loci in these backgrounds are poorly understood. A design‐II mating scheme including new temperate and subtropical lines produced 69 hybrids. Large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Broad sense heritability estimates for all three amino acids in maize are relatively lower than those for other phytochemicals (Mahan et al, 2014). Nevertheless, there were sufficient levels of variation at the heterotic group and population levels to discriminate between endosperm textures based on amino acid contents (Fig.…”
Section: Significance For Breeding Quality Maizementioning
confidence: 89%
See 3 more Smart Citations
“…Broad sense heritability estimates for all three amino acids in maize are relatively lower than those for other phytochemicals (Mahan et al, 2014). Nevertheless, there were sufficient levels of variation at the heterotic group and population levels to discriminate between endosperm textures based on amino acid contents (Fig.…”
Section: Significance For Breeding Quality Maizementioning
confidence: 89%
“…When compared with the original germplasm classification, the CDA results suggested that the ratio between translucent and opaque endosperm may possibly be revised upward from the original 0.613:0.387 to approximately 0.7:0.3, indicating that the breeding program already succeeded in developing populations, and accessions within populations, with the desirable combinations of amino acid content and endosperm texture (Pollak, 2003;Gutierrez-Rojas et al, 2008;Mahan et al, 2014). When compared with the original germplasm classification, the CDA results suggested that the ratio between translucent and opaque endosperm may possibly be revised upward from the original 0.613:0.387 to approximately 0.7:0.3, indicating that the breeding program already succeeded in developing populations, and accessions within populations, with the desirable combinations of amino acid content and endosperm texture (Pollak, 2003;Gutierrez-Rojas et al, 2008;Mahan et al, 2014).…”
Section: Discrimination Between Opaque and Translucent Endospermmentioning
confidence: 99%
See 2 more Smart Citations
“…Nixtamalization entails to an increase in maize amino acids bioavailability. Maize is deficient in lysine and tryptophan essential amino acids, resulting in a low nutritional quality protein (Mahan et al 2014). This deficiency has led the attention of research to improve the nutritional value of tortillas by supplementing them with pulses flours among others, however, this supplementation decrease significantly consumers acceptance.…”
Section: Introductionmentioning
confidence: 99%